Immunosenescence in atherosclerosis: A role for chronic viral infections - Ghamar Talepoor, Atefe; Doroudchi, Mehrnoosh (Frontiers in Immunology, 2022)
Immune system is a versatile and dynamic body organ which offers survival and endurance of human beings in their hostile living environment. However, similar to other cells, immune cells are hijacked by senescence. The ageing immune cells lose their beneficial functions but continue to produce inflammatory mediators which draw other immune and non-immune cells to the senescence loop. Immunosenescence has been shown to be associated with different pathological conditions and diseases, among which atherosclerosis has recently come to light. There are common drivers of both immunosenescence and atherosclerosis; e.g. inflammation, reactive oxygen species (ROS), chronic viral infections, genomic damage, oxidized-LDL, hypertension, cigarette smoke, hyperglycaemia, and mitochondrial failure. Chronic viral infections induce inflammaging, sustained cytokine signaling, ROS generation and DNA damage which are associated with atherogenesis. Accumulating evidence shows that several DNA and RNA viruses are stimulators of immunosenescence and atherosclerosis in an interrelated network. DNA viruses such as CMV, EBV and HBV upregulate p16, p21 and p53 senescence-associated molecules; induce inflammaging, metabolic reprogramming of infected cells, replicative senescence and telomere shortening. RNA viruses such as HCV and HIV induce ROS generation, DNA damage, induction of senescence-associated secretory phenotype (SASP), metabolic reprogramming of infected cells, G1 cell cycle arrest, telomere shortening, as well as epigenetic modifications of DNA and histones. The newly emerged SARS-CoV-2 virus is also a potent inducer of cytokine storm and SASP. The spike protein of SARS-CoV-2 promotes senescence phenotype in endothelial cells by augmenting p16, p21, senescence-associated β-galactosidase (SA-β-Gal) and adhesion molecules expression. The impact of SARS-CoV-2 mega-inflammation on atherogenesis, however, remains to be investigated. In this review we focus on the common processes in immunosenescence and atherogenesis caused by chronic viral infections and discuss the current knowledge on this topic.